Distribution and ecology of myxomycetes on Christmas Island, Indian Ocean - Stephenson, Steven L.; Stephenson, Barbara C. (Phytotaxa, 2019)
A survey for myxomycetes was carried out on Christmas Island in May 2017. Specimens included those that had fruited in the field under natural conditions and those appearing in moist chamber cultures prepared with samples of dead plant material collected on the island. Fifty-nine species in 18 genera were recorded. Hemitrichia serpula was the most common species represented among field collections, whereas Arcyria cinerea, Diderma effusum, Lamproderma scintillans, Didymium squamulosum, Diderma hemisphericum and Diachea leucopodia were recorded the most often in moist chamber cultures. These new records bring the total number of species of myxomycetes known from Christmas Island to 68 species in 22 genera. The distribution and ecology of these species in relation to the various substrates available to them are discussed.